Hubungan Riwayat Penyakit KEK, Pola Makan, dan Hiperemesis Gravidarum dengan Kejadian Kekurangan Energi Kronik Pada Ibu Hamil Puskesmas Dana Mulya Kecamatan Pulau Rimau Kabupaten Banyuasin Tahun 2021 - Nena Muryani; Eka Afrika; Eka Rahmawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Health problems in pregnant women are indeed complex problems. In Indonesia in 2017, there were 44,460 pregnant women with obstetric complications and a maternal mortality rate of 91 people per 100,000 live births. One of the factors for the high maternal mortality rate is the presence of high-risk pregnancies, namely, pregnancies accompanied by diseases or conditions that can have an adverse impact on the mother or fetus. Objective: To determine the relationship between history of KEK, diet, and hyperemesis gravidarum with the incidence of chronic energy deficiency in pregnant women at the Dana Mulya Health Center, Pulau Rimau, Banyuasin Regency in 2021. The research design that will be used in this study is descriptive analytic with a cross sectional approach. This research was carried out at the Dana Mulya Health Center, Rimau Island District, Banyuasin Regency. The sample in this study amounted to 56 respondents. The results of the bivariate analysis of the history of KEK variable obtained p-value 0.000, dietary variables obtained p-value 0.000, hyperemesis gravidarum variable obtained p-value 0.003. This means that the hypothesis is accepted that there is a relationship between hyperemesis gravidarum, history of SEZ, diet and the incidence of CED in pregnant women at the Dana Mulya Health Center, Rimau Island District, Banyuasin Regency in 2021.